Faktor-Faktor yang Mempengaruhi dan Dampak Pernikahan Dini di Desa Delu Depa Kecamatan Kodi Bangedo-Kabupaten Sumba Barat Daya - Bokol, Paulina; Kamidah Kamidah (Jurnal Rumpun Ilmu Kesehatan, 2025)
Background: Early marriage remains prevalent among adolescents aged 15–19 years, a period during which individuals are often medically and psychologically unprepared to assume marital responsibilities. Decisions to marry early are influenced by internal factors such as psychological readiness, emotional maturity, and critical thinking ability, as well as external factors including family pressure, cultural norms, and economic challenges. Objective: This study aims to explore the factors influencing adolescents' decisions to engage in early marriage and examine its impacts on their lives. Method: This research employed a qualitative descriptive design. A purposive sampling technique was used to select 10 adolescents who had experienced early marriage. Data were collected through in-depth interviews and document review, and analyzed thematically. Results: The primary factors contributing to early marriage in Delu Depa Village, Kodi Bangedo District, were premarital pregnancy (2 cases), economic hardship (4 cases), and limited educational attainment (4 cases). The consequences included psychological, health, and social impacts. Psychologically, participants reported experiencing stress, anxiety, and depression. Health-related risks included complications associated with immature reproductive organs, such as premature birth, obstructed labor, and preeclampsia. Social impacts included stigma, limited social interaction, school dropout, and employment in low-skilled jobs to fulfill daily needs. Conclusion: Early marriage poses significant risks to adolescents' psychological well-being, physical health, and social functioning. Strengthened preventive efforts and targeted interventions are needed to reduce its prevalence and mitigate negative consequences.